2007
DOI: 10.2139/ssrn.1073158
|View full text |Cite
|
Sign up to set email alerts
|

Selection into Financial Literacy Programs: Evidence from a Field Study

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Researchers have hypothesized that those who discount the future more heavily may be less willing to invest resources in acquiring financial knowledge, because such an investment has a delayed payoff. For instance, a recent study found that it is disproportionately those who are patient who self‐select into financial education programs (Meier and Sprenger 2007). As a proxy for time preference in this study, we used an indicator of whether a respondent had ever smoked.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have hypothesized that those who discount the future more heavily may be less willing to invest resources in acquiring financial knowledge, because such an investment has a delayed payoff. For instance, a recent study found that it is disproportionately those who are patient who self‐select into financial education programs (Meier and Sprenger 2007). As a proxy for time preference in this study, we used an indicator of whether a respondent had ever smoked.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have hypothesized that those who discount the future more heavily may be less willing to invest resources in acquiring financial knowledge, since such an investment has a delayed payoff. For instance, a recent study found that it is disproportionately those who are patient who self-select into financial education programs (Meier and Sprenger 2007). As a proxy for time preference in this study, we used an indicator of whether a respondent had ever smoked.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that several scholars who have published recent studies about financial literacy have not explicitly defined the concept (Chen and Volpe 2002; Meier and Sprenger 2007; Morton 2005; Servon and Kaestner 2008). This further confirms the need for a synthesized definition.…”
Section: Literature On Financial Literacymentioning
confidence: 99%